استخدام وسيلة "Quizziz" في تعلم اللغة العربية في مدرسة خير الدين الثانوية الإسلامية غوندانج ليغي مالانج : Penggunaan Aplikasi Quizziz pada Pembelajaran Bahasa Arab di MA Khoiruddin Gondanglegi Malang - Salma, Madian Fitri; Masruhani, Hasna'i; Nasution, Ali Fuddin; Hilmi, Danial (Shaut al Arabiyyah, 2022)
Abstract Nowadays, online learning is an educational system used in schools. This policy is accompanied by instructions for applying distance learning or online learning. To facilitate online learning, there are many learning support modes to facilitate the implementation of learning in the classroom. One of the related media is educational aids through Quizizz. This application is expected to add educational value and make students learn innovatively. This study aims to determine the use of Quizizz in learning Arabic in Khairuddin Gondang Legi Malang. This study uses descriptive qualitative research method.. The results of the study indicate that: The use of the Quizizz application in learning Arabic at Madrasah Aliyah Khairuddin Gondanglegi, Malang Regency, East Java, has become an innovation in learning that helps students learn online and also do assignments given by the teacher. In general, the use of the Quizizz application is almost the same as making the google form format, however, some only change in their content. One of the media to create a pleasant learning atmosphere but does not eliminate or reduce students' understanding of the material and take advantage of technological developments, is the application of games or games. Online games or games that can be used as an alternative in delivering learning materials to high school students, namely the Quizizz application. This educational game provides so many benefits that can certainly be felt in learning media, because this media is interesting and can motivate brain work and time management. Of course, in its application there are obstacles as well as solutions/alternatives that make it easier for teachers to learn. so that it can be a solution in learning. In fact, it can be a challenge for teachers and students in using technology. Keyword: Quizizz , methods learning Arabic.